PERFORMANCE ANALYSIS OF 19 AMBON STATE MIDDLE SCHOOL USING BALANCE SCORECARD APPROACH - Rudolf Kempa; Rosmaryn Tutupary (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
Performance analysis using the balance scorecard approach enables the acquisition of a comprehensive picture of its performance including the ability of schools to meet the satisfaction of education stakeholders (stakeholders). The use of the Balance Scorecard approach in measuring school performance is seen from 4 perspectives, namely financial perspective where schools are expected to provide better education services to the community, customer perspective where schools are expected to empower the community in decision making processes and evaluation of school performance evaluations, internal process perspectives where schools expected to provide results in accordance with the programs and activities that have been planned, as well as learning and growth perspectives where the school is expected to improve and create value, but in this study only limited to 2 perspectives, namely the customer perspective and learning and growth perspective. This study aims to determine: The performance of Ambon 19th Junior High School from the customer aspect, the performance of Ambon 19th Junior High School from the aspects of learning and growth. This research was carried out in Ambon 19 Junior High School in five months. The method used is a survey method with quantitative descriptive research type. The population of this study were all 19Ambon Junior High School students, amounting to 911 students and 911 parents. Sampling of this study was carried out using proportional random sampling technique which was carried out randomly in 3 classes namely 90 people and 90 students' parents. Data is collected through a Likert scale questionnaire instrument, which will be tested to determine the validity and reliability of the instrument. Data from the results of this study were analyzed with the SPSS program to determine school performance as seen from Physical Forms (Tangibles), Reliability, Responsiveness, Assurance and Empathy. From the results of the analysis and discussion it can be concluded that: The level of customer satisfaction (students) on school performance both on the five dimensions of service quality, namely: tangibility, reliability, responsiveness, assurance, and empathy have a very high level of satisfaction explained by 99% level satisfaction with school performance; and the level of customer satisfaction towards learning and growth oriented to employee satisfaction, alumni tracking and information systems have a very high level of satisfaction that can reach 98% very satisfied so that school performance is stated to be very good with a score of 85 scores